R/V NATSUSHIMA NT14-01 Cruise Data - JAMSTEC (JAMSTEC, 2014)
[CRUISE DATA] This site includes a cruise dataset acquired in NT14-01 on R/V NATSUSHIMA from 2014-02-04 to 2014-02-07.
Observation contents: Bathymetry, Expendable Bathythermograph
Keywords: Research cruise; R/V NATSUSHIMA; oceans